(Nie)codzienność innowacyjnej działalności nauczyciela = (Un)commonness of the teacher's innovative activity - Grzemna, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses innovative activities of the teacher. In the introduction I outline the topic, taking into account my subjective assessment of the prevalence of this phenomenon in education. Next, the article presents changes in education after R. Schulz, which show the complexity and multistepiness of the process. The need for innovation is also discussed, taking into account all aspects of modern education that function improperly and that require change and modernization. In the next part I explain the notion of ?creativity? and ?innovation?, taking into account the in terpretations of various authors with an indication of the important role of creativity in the process of innovation. I also present the most important motives of educators to introduce changes in education, and obstacles to their implementation. Finally, I point out the importance of innovative activities in modern education, which needs change in order to be able to teach better and develop students' motivation for learning
Keywords: zmiana; oświata; nauczyciele; uczeń; innowacja; twórczość; przyczyna; działania; potrzeba; przeszkoda; szkoła; postęp; rozwój; change; education; teacher; students; innovation; creativity; activity; cause; need; obstacle; school; progress; development